Analisis Koleksi Perpustakaan Berdasarkan Standar Perpustakaan Perguruan Tinggi (Studi kasus di Perpustakaan UIN Sunan Gunung Djati Bandung) - L. Nailah Hanum Hanany (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
This study aims to analyze the library collections of UIN Sunan Gunung Djati Bandung according to the National Library-University Standard (SNP-PT) and the Standard for Libraries in Higher Education. The research method uses descriptive qualitative. Data were collected by observing, in-depth interviews, analysis of various related documents, field notes, and triangulation. The results of the analysis show that based on the SNP-PT standard, the collection indicators that have met the standards include type and number, development, collection of local content, reference collection, and processing. The indicators for re-counting, weeding, preserving, and converting book collections to digital format have not been carried out as stipulated by the standard. Based on the Standard for Libraries in Higher Education, the collection indicators that have been met include the type and format of the collection, access to the collection, and the uniqueness of the collection. Meanwhile, the indicators for the availability of collections, processing infrastructure, information literacy, and the availability of long-term access have not met the standards due to the limited budget and number of human resources with special competencies in the field of information literacy and media transfer.